Time trend analysis of environmental contaminants in human Arctic populations - Nevala, Laura (UiT Norges arktiske universitet, 2022)
Background: Arctic Monitoring and Assessment Programme (AMAP) monitors persistent organic pollutant (POP) levels in the Arctic and assesses health effects related to them. Many of the POPs are regulated internationally, but still found in humans and biota. There are also new emerging contaminants, of which many are unregulated. Arctic populations present high contaminant concentrations compared to non-Arctic populations, with traditional food being the main source of exposure. Time trend analyses give information of effectiveness of international regulations, but also of warning of new emerging contaminants. Objectives: The objective of this study is to analyze time trends of 24 contaminants or their combination in Arctic populations including USA, Canada, Iceland, Faroe Islands, Greenland, Sweden, Norway, and Finland. Legacy POPs analyzed in this study include organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs), whereas per- and polyfluoroalkyl substances (PFAS) and polybrominated biphenyl ethers (PBDEs) are new emerging contaminants included in this study. Methods: Data included in this study is aggregated data presented in the AMAP Human Health in the Arctic 2021 assessment. AMAP assessments provide contaminant concentrations measured in maternal, adult and child blood and breast milk samples from different epidemiological studies conducted in the Arctic since 1980s. For some populations, where no new data was presented or it was presented as figures in AMAP 2021, AMAP 2009 and AMAP 2015 were used to collect data. Linear regression was used to assess time trends of the different POPs within different Arctic populations. Results: Overall decreasing time trends were observed for PCBs and OCPs in Arctic populations. Regulated PFAS showed declining trends, but increasing trends were observed for unregulated PFAS in certain populations. PBDEs showed decreasing or inconsistent trends. Conclusions: Declining trends are observed for legacy POPs, but the trends for new emerging contaminant are ...